Single-ion gel-polymer electrolyte for improving the performances of Li-ion batteries - Radu Dorin Andrei; Giorgian Cosmin Ungureanu; Luisa Roxana Mandoc; Soha Aldroubi; Nicolas Louvain; Julian Richard Tolchard; Mihaela Buga (Applied Surface Science Advances)
Solid State Batteries (SSBs) combine the significantly higher energy density (>450 Wh/kg) and enhanced safety required to expedite society's transition away from fossil fuels, making them the most potential ''next-gen'' chemistry for lithium-based batteries. However, issues with electrolyte performance at lower temperatures as well as issues with the effective deposition and stripping of metallic lithium anodes are now impeding their development. In this work, we suggest a completely new strategy to deal with these issues: creating a Solid Molecular Ionic Composite Electrolyte (SMICE), an entirely novel type of gel-polymer electrolyte. This new membrane exhibits outstanding ionic conductivity at room temperature (3.3 mS·cm-1). Following electrochemical tests, the symmetric lithium cells demonstrated long-term cycling stability of approximately 650 h at 25 °C and 1000 h at 60 °C. In half-cell configuration the specific discharge capacity reaches a maximum of 164 mAh·g-1 with a high retention of 95 % after 300 cycles, signifying the stability of SMICE membrane. These results reveal the proper compatibility between the SMICE membrane and the cell electrodes.